Implication of diffusion of microelectronics-based factory automation technology for human resource development : country report : Malaysia - Mohamed Shariff Nabi Baksh; Amir Abdullah; Imran Idris; Ahmad Yusoff Hassan; Conference on Innovation of Production Systems for in Manufacturing Industry (1994 : Singapore)
22